Proyecto de factibilidad para la implementación de una granja productora y comercializadora de tomate de árbol en el cantón Quijos, provincia de Napo, para el año 2015 - Díaz Zambrano, Irene Narcisa (2016)
This research for the "IMPLEMENTATION OF A PRODUCER FARM AND DISTRIBUTOR OF TOMATO TREE IN THE QUIJOS CANTON, PROVINCE OF NAPO, FOR 2015" was carried out with the purpose of promoting and encouraging the production of tomato tree in the Canton Quijos, being a product that every day is part of the fruit used in the feeding of citizenship, this product is well known and enjoys high demand not only for its taste but also for its nutritional and medicinal benefits. An overall objective and six specific objectives, in order to fulfill arose; once collected the field information through surveys both applicants and bidders Canton, was necessary to resort to various public institutions of the canton and the province to obtain reliable data, this data is used them in the development of different applied studies. To develop research the theoretical method with which definitions on the subject of research was pointed out, the descriptive method by which was analyzed and showed the issues raised, contributing to an analysis was used in each of the aspects that they formed the literature review, the Mathematical Method - Analytical was used for extraction and analysis of different data values obtained from surveys carried out in the research process, the deductive method with which the set of general statements was determined then deduct in conclusions consequences of project implementation. The technique of direct observation by going to different tomato plantations existing tree in the corner, in order to acquire more knowledge about the production process was applied. After developing all the studies that make up the research project it determined the following conclusions: Market research showed that there is unmet demand in the canton Quijos. The Technical Study determined the size of the project, its installed capacity and capacity utilization, also the optimal location, project engineering and production process. Organizational Study in administrative and legal structure that the company will meet the standards and requirements established in the laws of the Republic was designed. In the Financial Study the initial investment amount in USD $ 20.672,73 dollars of the United States was determined, who’s financing will be for the contribution of each partner's equity with a value of USD $ 6.945,25 States dollars States of America. Net Present Value (NPV) of the project is USD $ 19.320,09 dollars of the United States of America: In the financial evaluation the following results were obtained. Internal Rate of Return (IRR) obtained is 27.70%, higher than the rate of 9% capital cost percentage. Indicator Benefit Cost Ratio is 1.35 meaning that for every dollar invested a profit of USD $ USD 0.35 United States of America is obtained. With the results obtained it is determined that the time to recover the investment project 2 years, 8 months and 12 days. Sensitivity Analysis on the 10% increase costs 0.15 coefficient that is less than 1 was obtained which means that the project is not sensitive; in the sensitivity analysis with a revenue decline of 12% it was obtained as a result is less than 0.15 to 1, which means that the project is not sensitive, so the changes do not affect the profitability of the project. To finalize the Environmental Impact Study reflected the social aspect - economic will affect positively as it boost the economy, but the quality of air and soil will be negatively influenced by the frequent use of fungicides and pesticides.